Performance Evaluation of Electrical Transmission Line Detection and Tracking Algorithms Based on Image Processing Using UAV - Karakose, Ebru (Ieee, 2017)
Regular control of the electrical transmission lines is important in preventing unwanted accidents and power interruptions. It is very difficult to carry out this process involving the determination of the transmission line, the tower and the plants surrounding the transmission line with human power. Today, there are some studies that use unmanned aerial vehicles to control transmission lines. In this study, the performance evaluation of the algorithms required for monitoring and controlling the transmission lines with image processing is given by using unmanned aerial vehicles. For this, firstly the capabilities of the studies in the literature have been put forward and then inferences have been made on how to overcome the shortcomings of these studies. In addition, some application results on experimental images, necessary hardware architecture and algorithm structure to make line control healthy and highly accurate are given in detail. In particular, the examination of the required stability and control methods performances for the line control realization will contribute to the works in this area.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Transmission Line Fault; Image Processing; UAV; Line Detection; Line Inspection